1980
DOI: 10.1002/eji.1830100716
|View full text |Cite
|
Sign up to set email alerts
|

Surface proteins of Schistosoma mansoni and their expression during morphogenesis

Abstract: Surface components of Schistosoma mansoni have been identified by lactoperoxidasecatalyzed iodination. Cercariae have a simple labeling pattern in comparison to schistosomula. Transformation of cercariae to schistosomula results in the loss of a low molecular weight material which may be the glycocalyx, and the appearance of many more labeled proteins. Mechanical conversion of cercariae to schistosomula requires subsequent incubation at 37 degrees C for more than 1 h to give the full surface-labeling pattern o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(20 citation statements)
references
References 13 publications
2
17
0
1
Order By: Relevance
“…Several workers have reported the labeling of polypeptides on the surface of freshly transformed schistosomula by a variety of techniques (3,11,12,19,20). The results obtained, however, are largely inconsistent, due in part to the different specificities of the various labeling techniques utilized, but possibly also due to the way in which the parasites were treated, since even where the same techniques have been used different results have been obtained (3,11,19). Nevertheless, the general conclusion, that the exposed surface of schistosomula of S. mansoni is relatively complex, with a large number of surface proteins and no reproducibly dominant species, can be drawn from the available data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several workers have reported the labeling of polypeptides on the surface of freshly transformed schistosomula by a variety of techniques (3,11,12,19,20). The results obtained, however, are largely inconsistent, due in part to the different specificities of the various labeling techniques utilized, but possibly also due to the way in which the parasites were treated, since even where the same techniques have been used different results have been obtained (3,11,19). Nevertheless, the general conclusion, that the exposed surface of schistosomula of S. mansoni is relatively complex, with a large number of surface proteins and no reproducibly dominant species, can be drawn from the available data.…”
Section: Discussionmentioning
confidence: 99%
“…A considerable number of polypeptides have t Present address: Division of Parasitology, National Institute for Medical Research, The Ridgeway, Mill Hill, London NW7, United Kingdom. been detected on schistosomula by a variety of surface labeling techniques (3,11,12,19,20), and, indeed, some of these have been found to be antigenic as judged by immunoprecipitation with sera from animals or patients with chronic schistosome infections (3,20).…”
mentioning
confidence: 99%
“…The first results concerning the surface-labelling of adult schistosomes were reported by Hayunga et al (55), who showed that the Bolton-Hunter technique was the most suitable for the labelling of adult worm surface components. Snary et al also observed the relative inefficiency of the lactoperoxydase technique on the adult stages of schistosomes (94). The 1 2 5I-iodosulfanilic acid (101) or lactoperoxydase technique appeared very useful for the extrinsic labelling of the larval surface, allowing the identification of major schistosomulum surface antigens of 30-40 kDa and 15-25 kDa, recognized by serum obtained from chronically infected animals or humans and from animals immunized with irradiation-attenuated cercariae (46, 88,91,97,99).…”
Section: Characterization Of Schistosomulum Ta Rget Antigensmentioning
confidence: 96%
“…Theuseofiodosulphanilic acid was prompted by its successful labeling of human erythrocytes (Berg 1969) and by earlier failures in labeling schistosomula by the more conventional lactoperoxidase technique (Brink 1977, Ruppel 1978, Hayunga et al 1979a). More recently, however, Snary et al (1980) have succeeded in labeling at least 12 schistosomulum proteins by the lactoperoxidase method. Our results are in general agreement with those of Snary et al: the additional proteins identified by them probably reflect the use ofthe more sensitive autoradiographic technique.…”
Section: Butterworth Et Almentioning
confidence: 99%